Bioremediation Potential of Plant-Bacterial Consortia for Chlorpyrifos Removal Using Constructed Wetland - Aziz, Tahira; Rasheed, Sajida; Shah, Asad Hussain; Nasir, Habib; Fariq, Anila; Jamil, Asma; Jannat, Sammyia (Frontiers in Environmental Science, 2022)
The extensive and unchecked application of chloropyrifos against crop insects has caused contamination of various ecosystems like soil, sediments and water, posing harm to plants, animals, useful arthropods and humans. The present study aimed at evaluating the ability of proto-type constructed wetland to biodegrade chloropyrifos and its major metabolites especially2-hydroxy-3, 5, 6-trichloropyridine/ol (TCP) using chlorpyrifos degrading indigenous bacterial strains i.e., Acinetobacter baumanni and Bacillus cibi with Canna spps and indigenous Mentha spps as bacterial-plant consortium. Soil and plant samples were collected at regular time intervals for twelve weeks, analytes were extracted using toluene method and evaluated through gas chromatography-mass spectrometry (GC-MS). In case of wetland vegetation with Canna and Mentha, 2-hydroxy-3, 5, 6-trichloropyridine (TCP, m/z=198), 2- hydroxypyridine (m/z = 97) with deprotonated molecular ions at m/ z = 69 (M-H)−were detected as the intermediate metabolites while in bacterial-plant consortium, instead of TCP, a 3, 5, 6-trichloro-2-methoxypyridine (TMP, m/z=212) was formed, along with di-ethylthiophosphate (DETP, m/z=169). Based on the metabolite analysis using GC-MS, biodegradation pathway for chlorpyrifos degradation through bacterial-plant consortia is predicted. The constructed wetland with bacterial-plant consortium showed its potential to either bypass TCP generation, or TCP may have been immediately biodegraded by the plant part of the consortium. The designed constructed wetland provided a novel remedial measure to biodegrade chlorpyrifos without producing harmful metabolites.